Comparison of DNA Extraction Methods and Selection of Primer Sets for Sex Identification of the Red-Whiskered Bulbul (Pycnonotus jocosus) - Changtor, Phanupong; Yimtragool , Nonglak (International Journal of Poultry Science, 2020)
Background and Objective: The red-whiskered bulbul (Pycnonotus jocosus) is an avian species that is considered to have economic value. Problem of propagation are often encountered by breeders as birds of the same gender placed together do not mate and reproduce. Polymerase chain reaction (PCR), as a popular biomolecular technique was used to solve this problem. This study aimed to compare DNA extraction methods and select the primer sets for sex identification using PCR. Materials and Methods: A total of 5 (blood/feather calamus) samples were subjected to DNA extraction with different methods: blood using lysis buffer and feather calamus using lysis buffer and alkaline lysis. DNA fragments were performed by PCR using 4 primer sets CHD1F/CHD1R, 2550F/2718R, P2/P8 and P2/NP/MP. The PCR products of each primer set were sequenced to determine a map location of 4 primer sets on the chromo-helicase DNA-binding (CHD) gene. Results: The feather calamus with lysis buffer method rendered the highest DNA concentration. No statistically significant differences were found in the purity of DNA obtained from the three methods of extraction. Extracted DNAs were used in sex identification at 100% usability. Results showed the CHD1F/CHD1R and P2/P8 primer sets accurately identified the sex of the red-whiskered bulbul, while the CHD1F/CHD1R more clearly separated PCR products by agarose gel electrophoresis compared with the other three primers. Conclusion: CHD1F/CHD1R was identified as a suitable primer for sex identification in this species and may also be applied to related species.